2020
DOI: 10.1002/jso.26200
|View full text |Cite
|
Sign up to set email alerts
|

Management of the positive sentinel lymph node in the post‐MSLT‐II era

Abstract: Background and Objectives: The publication of MSLT-II shifted recommendations for management of sentinel lymph node biopsy positive (SLNB+) melanoma to favor active surveillance. We examined trends in immediate completion lymph node dissection (CLND) following publication of MSLT-II. Methods: Using a prospective melanoma database at a high-volume center, we identified a cohort of consecutive SLNB+ patients from July 2016 to April 2019. Patient and disease characteristics were analyzed with multivariate logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…These two practice-changing trials lead to a change in national guidelines, and effective as of January 2018, we abandoned ILND for micrometastatic disease in Denmark 12 . This caused a sharp decline in the number of ILND procedures performed, which is consistent with international treatment patterns 17 , 18 , 19 . The MSLT-II trial also showed that 25% of patients with micrometastatic disease undergoing observation would experience locoregional lymph node recurrence and later require lymph node dissection.…”
Section: Discussionsupporting
confidence: 75%
“…These two practice-changing trials lead to a change in national guidelines, and effective as of January 2018, we abandoned ILND for micrometastatic disease in Denmark 12 . This caused a sharp decline in the number of ILND procedures performed, which is consistent with international treatment patterns 17 , 18 , 19 . The MSLT-II trial also showed that 25% of patients with micrometastatic disease undergoing observation would experience locoregional lymph node recurrence and later require lymph node dissection.…”
Section: Discussionsupporting
confidence: 75%
“…17,27 Notably, this finding is mirrored by the rapid deimplementation of completion lymph node dissection in patients with melanoma after the Multicenter Selective Lymphadenectomy Trial-II (MSLT-II) demonstrated no overall survival benefit. 28,29 Additionally, clinicians have cited the strong evidence base and wide dissemination of the Z0011 trial for ALND and SSO/ASTRO recommendation of a negative margin as "no tumor on ink" as reasons why these practices have decreased. 17,30,31 This is supported by our study, which found considerable variation in ALND and lumpectomy reoperation rates by facility type before the respective guidelines but minimal variation afterwards, suggesting these recommendations provided clarity on appropriate indications for ALND and lumpectomy reexcision where there had previously been uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…For ALND, both surgeons and patients viewed lymphedema risk as significant, which likely contributes to eagerness to omit ALND . Notably, this finding is mirrored by the rapid deimplementation of completion lymph node dissection in patients with melanoma after the Multi-center Selective Lymphadenectomy Trial-II (MSLT-II) demonstrated no overall survival benefit . Additionally, clinicians have cited the strong evidence base and wide dissemination of the Z0011 trial for ALND and SSO/ASTRO recommendation of a negative margin as “no tumor on ink” as reasons why these practices have decreased .…”
Section: Discussionmentioning
confidence: 99%
“…The pace of CLND de-implementation was swift in the two years after MSLT II publication, demonstrating a much shorter time to practice change than the average 17 years often cited in implementation research. [15][16][17] Rates of CLND at this study initiation and in prior studies demonstrate that CLND was already being performed selectively, perhaps due to a preexisting acknowledgement of the limitations of CLND, its associated risk of potentially life-altering lymphedema, or surgeons' lack of comfort with performing the procedure. 18,19 Before MSLT-II publication, several large retrospective cohort studies already suggested limited benefit of CLND, with most patients having no additional positive (non-sentinel) nodes in CLND specimens.…”
Section: Discussionmentioning
confidence: 86%